Finding Ashley : a novel - Steel, Danielle (New York : Delacorte Press, 2021)
"The story of two strong, brave women turning wretching loss into reconnection, and a family reunited after bringing dark secrets into the light."--
Keywords: Families -- Fiction; Grief -- Fiction; Friendship -- Fiction; Success -- Fiction; Domestic fiction